Harnessing the Strengths of Blended Learning - Papa, Elena (My University, 2021)
In the recent years, due to the pandemic, the use of the internet has become a necessity in almost every aspect of ordinary life. The education institutions are engaged either in online or blended learning teaching as the physical contact between human is banned to prevent virus spreading. This article charts the concerns related to blended learning as reﬂected in the educational literature. It is argued that, to appreciate the potential and limitations of blended learning in education, we need to trace what harness the strengths of the blended learning. The study applied the integrative review method, which involved reviewing the current literature in the implementation of blended learning. The research questions that guided the study were about the learners’ characteristics and needs in blended learning, the design features that should be considered in blended learning and finally which application of self-regulated learning is possible in blended learning. The recommendations justified by the research will be addressed to educators, designers of the education system aiming the advancement of effective blended learning environments. This study shows that students have a high potential of learning and retaining academic content through blended learning, especially concerning demonstrating learner self-regulation. Blended Learning aims to enhance student learning and develop crucial analytical skills and learning competencies. Our findings confirm that learners' ability to assess and critically assess knowledge sources accompanied by face-to-face support, interaction with peers, motivation and satisfaction of the learners is provided.
Keywords: E-learning; Education; Covid-19; Learner; Education institution